Genomic and Physiological Analysis of Carbon Storage in the Verrucomicrobial Methanotroph “Ca. Methylacidiphilum Fumariolicum” SolV - Khadem, Ahmad Fouad; van Teeseling, Muriel C.; van Niftrik, Laura; Jetten, Mike S.; Op Den Camp, Huub J.; Pol, Arjan (Frontiers in Microbiology, 2012)
“Candidatus Methylacidiphilum fumariolicum” SolV is a verrucomicrobial methanotroph that can grow in extremely acidic environments at high temperature. Strain SolV fixes carbon dioxide (CO2) via the Calvin-Benson-Bassham cycle with methane as energy source, a trait so far very unusual in methanotrophs. In this study, the ability of “Ca. M. fumariolicum” to store carbon was explored by genome analysis, physiological studies and electron microscopy. When cell cultures were depleted for nitrogen, glycogen storage was clearly observed in cytoplasmic storage vesicles by electron microscopy. After cessation of growth, the dry weight kept increasing and the bacteria were filled up almost entirely by glycogen. This was confirmed by biochemical analysis, which showed that glycogen accumulated to 36% of the total dry weight of the cells. When methane was removed from the culture, this glycogen was consumed within 47 days. During the period of glycogen consumption, the bacteria kept their viability high when compared to bacteria without glycogen (from cultures growing exponentially). The latter bacteria lost viability already after a few days when starved for methane. Analysis of the draft genome of “Ca. M. fumariolicum” SolV demonstrated that all known genes for glycogen storage and degradation were present and also transcribed. Phylogenetic analysis of these genes showed that they form a separate cluster with “Ca. M. infernorum” V4, and the most closely related other sequences only have an identity of 40%. This study presents the first physiological evidence of glycogen storage in the phylum Verrucomicrobia and indicates that carbon storage is important for survival at times of methane starvation.